Nailfold Capillaroscopy Abnormalities Correlate With Disease Activity in Adult Dermatomyositis - Johnson, Dylan; van Eeden, Charmaine; Moazab, Naima; Redmond, Desiree; Phan, Cecile; Keeling, Stephanie; Gniadecki, Robert; Cohen Tervaert, Jan Willem; Osman, Mohammed (Frontiers in Medicine, 2021)
Objectives The aim of this study was to determine the relationship between disease activity in adult patients with dermatomyositis (DM) and other biomarkers of disease activity such as C-reactive protein creatinine kinase and nailfold video capillaroscopy (NVC). Methods We performed a prospective single center study of 15 adult patients with DM. Study participants underwent two assessments at least nine months apart including clinical, laboratory and NVC evaluations. Patients received immunosuppressive medications for their dermatomyositis, and ongoing disease activity was measured by the Myositis Intention to Treat Index (MITAX). NVC evaluation included assessment of capillary density, capillary apical diameter (mm), and the number of microhemorrhages per digit. Results Microvascular abnormalities were present in most DM patients. Of these, capillary density (4.71 vs 6.84, p=0.006) and mean apical diameter (56.09µm vs 27.79µm, p=0.003) significantly improved over the study period in concordance with improving disease control (MITAX 8.53 vs. 2.64, p=0.002). Longitudinal analysis demonstrated that capillary density was independently associated with MITAX (β= -1.49 [CI -2.49, -0.33], p=0.013), but not other parameters such as C-reactive protein and creatinine kinase. Conclusions Nailfold capillary density is a dynamic marker of global disease activity in adult DM. NVC may be utilized as a non-invasive point-of-care tool to monitor disease activity and inform treatment decisions in patients with DM.